2019
DOI: 10.1029/2019ja026707
|View full text |Cite
|
Sign up to set email alerts
|

Solar Illumination Dependence of the Auroral Electrojet Intensity: Interplay Between the Solar Zenith Angle and Dipole Tilt

Abstract: The present study investigates the dependence of the local auroral electrojet (AEJ) intensity on solar illumination by statistically examining northward geomagnetic disturbances in the auroral zone in terms of the solar zenith angle χ. It is found that on the dayside, both westward and eastward electrojets (WEJ and EEJ) are more intense for smaller χ, suggesting that the solar extreme ultraviolet‐induced conductance is the dominant factor for the AEJ intensity. On the nightside, in contrast, the χ dependence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…The results shown in Fig. 7 are in agreement with the findings by Ohtani et al (2019) that "the nightside westward electrojet (WEJ) is more intense when the ionosphere is dark. "…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results shown in Fig. 7 are in agreement with the findings by Ohtani et al (2019) that "the nightside westward electrojet (WEJ) is more intense when the ionosphere is dark. "…”
Section: Discussionsupporting
confidence: 90%
“…With the removal of such fluctuations, the global-scale patterns are consistent and repeatable. For example, the electric potential patterns obtained from double-probe measurements on the Dynamics Explorer 2 satellite (Weimer, 1995(Weimer, , 2005a are very similar to results obtained from ground radar Greenwald, 1996, 2005;Cousins and Shepherd, 2010), an electron drift instrument on the Cluster spacecraft (Haaland et al, 2007), and ion drift meters on the DMSP (Papitashvili and Rich, 2002). The field-aligned current maps obtained from different data sets are also similar and repeatable.…”
Section: Discussionsupporting
confidence: 69%
“…Their seasonal variations are consistent with our results, whereas the local time differences are due to the narrower MLT sectors concentrated in their study. Ohtani et al (2019) found that in the daytime, both eastward and westward electrojets were more intense when the SZA was smaller, and in the midnight-to-dawn sector, the eastward electrojet was more intense for smaller SZA. These findings are consistent with our results.…”
Section: Ionospheric Conductance Effectmentioning
confidence: 90%
“…Ohtani et al. (2019) provided us with an in‐depth understanding of the formation of the auroral electrojet. However, Guo et al.…”
Section: Introductionmentioning
confidence: 99%
“…The auroral crochet is most likely caused by the modification of a pre-existing ionospheric current (or electrojet) by the enhanced electron density (Pudovkin, 1974). This effect increases as background plasma convection (ionospheric electric field) increases and, hence, is most visible during the polar disturbances of DP1 and DP2 (Akasofu, 1964;Nishida, 1968), as long as the ionosphere is sunlit, for example, near summer solstice when X-ray flux reaches high latitudes.…”
Section: Introductionmentioning
confidence: 99%